BitTorrent based transmission of real-time scalable video over P2P networks - Rodrigues, P. L. (2015)
The number of software applications available on the Internet for distributing video streams in real time over P2P networks has grown quickly in the last two years. Typical this kind of distribution is made by television channel broadcasters which try to make their content globally available, using viewer's resources to support a large scale distribution of video without incurring in incremental costs. However, the lack of adaptation in video quality, combined with the lack of a standard protocol for this kind of multimedia distribution has driven content providers to basically ignore it as a solution for video delivery over the Internet. While the scalable extension of the H.264 encoding (H.264/SVC) can be used to support terminal and network heterogeneity, it is not clear how it can be integrated in a P2P overlay to form a large scale and real time distribution. In this paper, we start by defining a solution that combines the most popular P2P file-sharing protocol, the Bit Torrent, with the H.264/SVC encoding for a real-time video content delivery. Using this solution we then evaluate the effect of several parameters in the quality received by peers.